How important is embeddedness in predicting Australian speech–language pathologists' intentions to leave their jobs and the profession?. (4th March 2019) - Heritage, Brody; Quail, Michelle; Cocks, Naomi
Abstract: Purpose : This study explored the predictors of the outcomes of turnover and occupation attrition intentions for speech-language pathologists. The researchers examined the mediating effects of job satisfaction and strain on the relationship between stress and the latter outcomes. Additionally, the researchers examined the importance of embeddedness in predicting turnover intentions after accounting for stress, strain and job satisfaction. Method : An online questionnaire was used to explore turnover and attrition intentions in 293 Australian speech–language pathologists. Result : Job satisfaction contributed to a significant indirect effect on the stress and turnover intention relationship, however strain did not. There was a significant direct effect between stress and turnover intention after accounting for covariates. Embeddedness and the perceived availability of alternative jobs were also found to be significant predictors of turnover intentions. The mediating model used to predict turnover intentions also predicted occupation attrition intentions. The effect of stress on occupation attrition intentions was indirect in nature, the direct effect negated by mediating variables. Qualitative data provided complementary evidence to the quantitative model. Conclusion : The findings indicate that the proposed parsimonious model adequately captures predictors of speech–language pathologists' turnover and occupation attrition intentions. Workplaces and the profession may wish to consider these retention factors.